[18F]mFBG PET/CT surpasses [18F]FDG PET/CT for evaluation of pediatric neuroblastoma - Zhang, Wenqian; Yang, Chao; Zhao, Zhenzhen; Zhou, Shunhao; Han, Yanyao; Zheng, Chenxi; Xiong, Yalan; Li, Changchun; Zhang, Yao; Wang, Zhenni; Cai, Liang; Wang, Shan (Frontiers in Oncology, 2025)
Purpose[18F]FDG PET/CT serves as an alternative imaging modality for neuroblastoma in cases where [123I]MIBG yields negative results or is unavailable. [18F]mFBG, a novel PET tracer for neuroblastoma imaging, requires further clinical validation. This preliminary study aims to evaluate the efficacy of [18F]mFBG PET/CT compared to [18F]FDG PET/CT in detecting neuroblastoma.MethodsIn this retrospective investigation, 56 pediatric patients were enrolled. Each patient underwent both [18F]mFBG PET/CT and [18F]FDG PET/CT within one week. Two children underwent a second paired [18F]FDG-[18F]mFBG PET/CT scan. In total, 58 paired scans (mean age 47.6 ± 38.0 months, range 6–108 months) were performed. Two experienced readers measured normal organ uptake (SUVmean), lesion uptake (SUVmax), and tumor-to-background ratio (TBR). A lesion-by-lesion analysis was conducted to compare detection rates between [18F]mFBG and [18F]FDG.ResultsTwenty paired scans exhibited negative findings on both [18F]mFBG and [18F]FDG studies. Among the remaining 38 scans, 8 (21.05%) were [18F]mFBG-positive/[18F]FDG-negative, 1 (2.63%) was [18F]FDG-positive/[18F]mFBG-negative, and 29 (76.32%) were positive on both tracers. In these 38 scans, [18F]mFBG PET/CT identified 431 lesions, whereas [18F]FDG PET/CT detected only 162 lesions (p<0.001). Six of eight [18F]mFBG-positive/[18F]FDG-negative cases were histopathologically confirmed as neuroblastoma. The mean TBR of [18F]mFBG PET/CT(6.68 ± 5.76) was significantly higher (p<0.001) than that of [18F]FDG PET/CT (4.49 ± 2.88).Conclusion[18F]mFBG PET/CT detected more neuroblastoma lesions than [18F]FDG PET/CT, suggesting it may be a more viable alternative when standard [123I]MIBG scanning is not feasible.